A surface quality improvement apparatus for ABS parts fabricated by additive manufacturing. Issue 1 (March 2017) - Kuo, Chil; Wang, Chen-Wei; Lee, Yi-Feng; Liu, Yan-Lin; Qiu, Qiao-Yi
Abstract Minimizing the surface roughness of physical models is a promising research issue in the field of additive manufacturing. An apparatus for enhancing the surface quality of the parts fabricated by additive manufacturing was developed in this study. The surfaces of the parts fabricated by additive manufacturing with different tilt angles, different curvatures, different aspect ratios, and low-pressure wax injection mold were treated by vapors of acetone using the developed apparatus. The developed apparatus is an excellent substitute for the manual polishing that is widely used in the industry currently. The advantages of this apparatus include ease of operation, no waste chemicals, and low costs. The surface quality improvement rate for low-pressure wax injection mold is about 88.82 %. The maximum aspect ratio for surface quality improvement is about 5.2. The surface quality improvement rate for parts with different curvatures is about 83–90 %. In addition, the surface quality improvement rate for parts with different tilt angles is about 84–96 %.